If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 + -32 = 43 + -7x Combine like terms: -12 + -32 = -44 -44 = 43 + -7x Solving -44 = 43 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -44 + 7x = 43 + -7x + 7x Combine like terms: -7x + 7x = 0 -44 + 7x = 43 + 0 -44 + 7x = 43 Add '44' to each side of the equation. -44 + 44 + 7x = 43 + 44 Combine like terms: -44 + 44 = 0 0 + 7x = 43 + 44 7x = 43 + 44 Combine like terms: 43 + 44 = 87 7x = 87 Divide each side by '7'. x = 12.42857143 Simplifying x = 12.42857143
| 7/12=25/x | | 4(5x-3)=12(x-1) | | X/5+3=23 | | 2x+4y=148 | | -6.79+0.27x=29 | | 5y+8=3Y-2 | | X/4+3=23 | | -4a-8=a+12 | | 2x+37=2x-43 | | -9=d/4 | | 1x+4y=50.50 | | 3.5(-7)=x | | 3/5+3=23 | | x^3-10x^2+22x=0 | | 10x^2y-14xy^2-15x+21y=0 | | 6(13-x)+4x=62 | | 5(x+2)-3(x-1)=33 | | 4(x+3)-2x=5x-3(x-4) | | -3+p=9 | | 7x+17=360 | | (-x)-(-3x)x= | | -5z+24=2z+3 | | 0=(12x^2)-42x+36 | | 3x-(-4x)x= | | -1/(2y-1) | | 0=(12x^2)-42x-36 | | 1/6x=y | | 7(x+1)-5=6x+11 | | y=1.81(1995)-3595 | | 2x-9/7=11 | | 2x+2=2(x+3) | | 2y-6=32y+24 |